Low‐intensity pulsed ultrasound ameliorates depression‐like behaviors in a rat model of chronic unpredictable stress. (28th October 2020) - Zhang, Jinniu; Zhou, Hui; Yang, Jian; Jia, Jun; Niu, Lili; Sun, Zuoli; Shi, Dandan; Meng, Long; Qiu, Weibao; Wang, Xiaomin; Zheng, Hairong; Wang, Gang
Abstract: Introduction: There is an unmet need for better nonpharmaceutical treatments for depression. Low‐intensity pulsed ultrasound (LIPUS) is a novel type of neuromodulation that could be helpful for depressed patients. Objective: The goal of this study was to investigate the feasibility and potential mechanisms of LIPUS in the treatment of depression. Methods: Chronic unpredictable stress (CUS) was used to generate rats with depression‐like features that were treated with four weeks of LIPUS stimulation of the ventromedial prefrontal cortex. Depression‐like behaviors were assessed with the sucrose preference, forced swim, and open field tests. BDNF/mTORC1 signaling was examined by Western blot to investigate this potential molecular mechanism. The safety of LIPUS was evaluated using hematoxylin‐eosin and Nissl staining. Results: Four weeks of LIPUS stimulation significantly increased sucrose preference and reduced forced swim immobility time in CUS rats. LIPUS also partially reversed the molecular effects of CUS that included decreased levels of BDNF, phosphorylated tyrosine receptor kinase B (TrkB), extracellular signal‐regulated kinase (ERK), mammalian target of rapamycin complex 1 (mTORC1), and S6 kinase (S6K). Moreover, histological staining revealed no gross tissue damage. Conclusions: Chronic LIPUS stimulation can effectively and safely improve depression‐like behaviors in CUS rats. The underlying mechanisms may be related to enhancement of BDNF/ERK/mTORC1 signaling pathways in the prefrontal cortex (PFC). LIPUS is a promising noninvasive neuromodulation tool that merits further study as a potential treatment for depression. Abstract : Four weeks repetitive transcranial low intensity pulsed ultrasound stimulation ameliorates depression‐like behaviors in a depression model of chronic unpredictable stress.